The study on the impact of short video tourism Vloggers at social media platform on online sharing intention - Zhao, Chen; Shen, Huawen; Zhang, Yating (Frontiers in Psychology, 2022)
COVID-19 has caused significant damage globally, including tourism. This study adopts the quantitative research method, selects 588 samples from tourists watching short videos to investigate the antecedents and effects of parasocial interaction between tourists and short video tourism Vloggers, and analyses them with partial least squares. Based on parasocial relationship theory, this study investigates the antecedents of parasocial relationships between tourists and short video tourism Vloggers and their willingness to share short video tourism. Results show that the consistency of values, entertainment motivation, and emotional engagement positively impact the parasocial relationships between tourists and short video tourism Vloggers and affect the online sharing intention through the parasocial relationship. The consistency of values can directly affect sharing intention. As an intermediary variable, parasocial relationship positively impacts value congruence, entertainment motivation, emotional engagement, and sharing intention. This study introduces parasocial relationship into the research of tourism short video Vloggers, which enriches the literature. Furthermore, this introduction provides new marketing strategies and suggestions for the sustainable development of tourism.